Magi på en runepinne fra Bryggen - Torgilstveit, Terje (Tidsskrift for kulturforskning, 2018)
This article looks at the runic inscription N636 (B407) from Bryggen in Bergen. It examines the different parts of this inscription and compare them with texts from younger grimoires. In addition, the article attempts to explain the corrupt forms in the inscription, such as "uasus" for "iesus", as misinterpretations of an original, which must also have been written in runes. The comparison of the inscription with material from grimories shows that the inscription probably originates in a tradition that can be labelled as learned or ritual magic. This type of magic was mainly based on Christian and Jewish mysticism, combined with elements from Greek and Egyptian magic, and this tradition presupposes that a practitioner at least has an elementary knowledge of Latin. The younger material that has most similarities with N636 is found in texts that one can describe as rituals of conjuration or summoning. The elements of conjuration and binding are missing in N636, and it is therefore likely that the full and undamaged inscription only contained a reduced version of a conjuration ritual. The inscription may therefore have been used as a talisman, which could have been thought to protect against demons and evil spirits or the diseases and misfortunes that these could cause.